RELIGIOUS PLURALISM AND THE POLITICS OF PUBLIC SYMBOLS IN NIGERIA:IMPLICATIONS FOR NATIONAL UNITY - John Clerk Koko; Gabriel Aduma Odey (AFRICAN JOURNAL OF RELIGION, CULTURE AND SOCIETY 3141-4370, 2026)
Nigeria's multi-religious and multi-ethnic character makes the managementof public symbols a critical issue in the pursuit of national integration andpolitical stability. In recent decades, the increasing visibility andinstitutionalization of religious symbols within public spaces and statestructures have generated intense debates regarding constitutionalneutrality, religious pluralism, and inclusive citizenship. While nationalsymbols such as the Nigerian flag, national anthem, coat of arms, andnational pledge were historically designed to foster collective identity andpatriotic consciousness, they appear to receive diminishing civic attention incomparison to religious symbols and loyalties. This study criticallyexamines the politics of religious and national symbols in 21st-centuryNigeria and evaluates their implications for national integration. Employingqualitative methodology through philosophical, historical, and sociopolitical analysis, the paper interrogates the symbolic presence of religion instate institutions, including the use of Arabic inscriptions on the nationalcurrency, the constitutional recognition of Sharia courts, and theincorporation of Islamic architectural motifs in public institutions. The studyargues that the disproportionate visibility of particular religious symbolswithin public spaces may contribute to perceptions of exclusion, deepenidentity-based tensions, and weaken the development of a shared nationalconsciousness in a religiously pluralistic society. The paper further contendsthat the declining emphasis on national symbols undermines civicnationalism and collective patriotism. It concludes by advocating inclusivesymbolic representation, constitutional fairness, and the revitalization ofnational symbols as essential instruments for promoting national unity,democratic coexistence, and sustainable integration in Nigeria.